Biomechanical comparison of the effects of anterior, posterior and transforaminal lumbar interbody fusion on vibration characteristics of the human lumbar spine. Issue 5 (4th April 2019) - Fan, Wei; Guo, Li-Xin
Abstract: Previous studies have compared the effects of different interbody fusion approaches on biomechanical responses of the lumbar spine to static loadings. However, very few have dealt with the whole body vibration (WBV) condition that is typically present in vehicles. This study was designed to determine the biomechanical differences among anterior, posterior and transforaminal lumbar interbody fusion (ALIF, PLIF and TLIF) under vertical WBV. A previously developed and validated finite element (FE) model of the intact L1–sacrum human lumbar spine was modified to simulate ALIF, PLIF and TLIF with bilateral pedicle screw fixation at L4–L5. Comparative studies on dynamic responses to the axial cyclic loading in these developed models were conducted. The results showed that at the fused L4–L5 level, dynamic responses of the von-Mises stress in L4 inferior and L5 superior endplates for the ALIF, PLIF and TLIF models were increased compared with the intact model. The endplate stresses in the TLIF model were lower than in the ALIF and PLIF models, but the TLIF generated greater stresses in the screws and rods compared with the ALIF and PLIF. At other levels, a decrease in dynamic responses of the disc bulge, annulus stress and intradiscal pressure was observed in all the fusion models compared with the intact one, but there was no obvious difference in these dynamic responses among the ALIF, PLIF and TLIF models. These findings might be useful in understanding vibration characteristics of the whole lumbar spine after different types of fusion surgery.